Qualitative Evaluation of Cancer Survivors’ Experiences of Metacognitive Therapy: A New Perspective on Psychotherapy in Cancer Care - Cherry, Mary Gemma; Salmon, Peter; Byrne, Angela; Ullmer, Helen; Abbey, Gareth; Fisher, Peter L. (Frontiers in Psychology, 2019)
Purpose: Preliminary evidence suggests that metacognitive therapy (MCT), a brief, process-focused psychological intervention, alleviates distress in cancer survivors. In a longitudinal qualitative study nested in an open trial of MCT for cancer survivors, we explored how patients understood, experienced and applied MCT. Methods: Patients received six MCT sessions. Consenting patients provided semi-structured interviews post-intervention (n=19), and at 3- and 6-months follow-up (n=14 and 10 respectively). Interviews were audio-recorded and transcribed. Analysis followed a constant comparison approach. Results: Participants felt ”overwhelmed” by worry before starting MCT and doubted that such brief therapy could help. Their accounts focused on feeling “challenged” to think differently by the psychologist. Those completing therapy were enthusiastic about it. They described having learned that thoughts are “only thoughts”, that feelings of worry or sadness are a normal part of life, and that they were in control of whether and how they engaged with thoughts. Consequently, most described a sense of freedom to live free from worry. A minority described being unable to apply MCT to certain thoughts. Two patients who withdrew before completing MCT did not describe having learned what MCT was intended to achieve. Conclusions: MCT is an acceptable brief intervention for distressed cancer survivors. Feeling challenged to understand the processes maintaining their distress was central to their enthusiasm for it, irrespective of their presenting difficulties. Implications for Cancer Survivors: The complexity of emotional distress in cancer survivors can potentially be addressed using a transdiagnostic model which focuses on the psychological processes which maintain distress.